Developing water quality retrieval models with in situ hyperspectral data in Poyang Lake, China. Issue 4 (1st October 2016) - Chen, Fangyuan; Xiao, Di; Li, Zhuochao
Abstract: Applying remote sensing techniques to develop the retrieval models and further to obtain the spatiotemporal information of water quality parameters is necessary for understanding, managing, and protecting lake ecosystems. This study aimed to calibrate and validate the retrieval models for estimating the concentrations of chlorophyll a ( C CHL ), suspended particulate matter ( C SPM ), and dissolved organic carbon ( C DOC ) with the in situ hyperspectral measurements in Poyang Lake, China in 2010 and 2011. The model calibration and validation results indicated that: (1) for C CHL retrieval, significantly strong and moderate correlations existed between the measured and estimated values (with the correlation coefficient r = 0.92 and r = 0.76) using the exponential model and the three-band model, respectively, with biased estimation observed for the exponential model; (2) for retrieving C SPM, there was a strong correlation between the measured and estimated values ( r = 0.95) using the exponential model; and (3) no significant correlation between measured and estimated C DOC values was found with our developed models. More work is needed to allow the water quality of Poyang Lake to be accurately and steadily estimated, especially for C CHL and C DOC .